The Role of Teacers in Adressing Bullying Among Fifth Grade Students - Ummi Latifah Anis Ma'Shumah; Muhammad Misbahul Munir (Journal of Education Action Reseach, 2026)
Bullying in elementary schools represents a serious and escalating concern that directly affects students’ psychological, social, and academic development. This study aims to analyze the roles undertaken by teachers in addressing bullying among fifth-grade students, encompassing preventive efforts, intervention strategies during incidents, and follow-up actions provided to both victims and perpetrators. A descriptive qualitative research design was employed. The primary participants consisted of two fifth-grade teachers from Class A and Class B, while supporting participants included 23 students from Class A and 21 students from Class B. Data were collected through observations, interviews, and documentation. Data analysis followed an interactive model comprising three stages: data reduction, data display, and conclusion drawing/verification. The findings reveal that bullying at SDN 1 Karangaji Jepara manifests in three primary forms physical, verbal, and social each exerting significant negative effects on students’ psychological well-being and learning motivation. The results further demonstrate that teachers played a pivotal and effective role in addressing bullying through individualized strategies implemented in Class V A and a collective, class-based approach applied in Class V B. These strategies enhanced students’ willingness to report incidents, fostered empathy, and contributed to a safer classroom environment. The study underscores the critical importance of strengthening teachers’ roles and promoting sustained collaboration between schools and parents to establish safe, inclusive, and supportive learning environments.